Konsep Pendidikan Islam Berbasis Fitrah: Studi tentang Pengembangan Potensi Diri Peserta Didik - Irwan Supriyanto; Amany Amany (STAI Al-Mas'udiyah, 2025)
This study aims to examine the concept of fitrah-based Islamic education and its relevance in developing students' potential. The research method used is a literature study with a qualitative approach, collecting and analyzing data from primary and secondary sources such as the Qur'an, Hadith, and the thoughts of Islamic education experts. The results of the study show that fitrah-based education emphasizes the development of students' potential holistically, covering spiritual, intellectual, emotional, and social aspects. This concept is in line with the principle of tawhid, which views humans as beings who have a natural tendency to know Allah (QS. Ar-Rum: 30). Fitrah-based Islamic education also integrates moral values, creativity, and independence in the learning process. The implication of this research is the importance of educators to understand the characteristics of students' nature in order to design learning methods that suit their needs and talents. Thus, Islamic education does not only focus on the transfer of knowledge, but also on the formation of a balanced personality and noble character.